Analisis Faktor Predisposing Terhadap Pemanfaatan Posyandu Balita di Wilayah Kerja Puskesmas Tegal Binangun Kota Palembang - Citrasari Syarkowi; Misnaniarti Misnaniarti; M. Zulkarnain (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: The proportion of Posyandu utilization by infants decreases with age of the child. Tegal Binangun Puskesmas has the lowest coverage of posyandu visits (D / S), amounting to 66.30% of 41 puskesmas in Palembang..Methods: An analytical research was conducted with cross sectional design in December 2019 - February 2020. The population of the study was 1,909 children under five years old in the working area of Tegal Binangun Public Health Center in Palembang. The research sample was mothers of toddlers 12 - 59 months in the working area of the Tegal Binangun Public Health Center in Palembang. 189 samples were selected by proportional random sampling. Data collection instruments are data collection papers that contain research variables. Data is taken from questionnaires about respondents' predisposing factors and direct observation of posyandu register books and KIA books. Data were analyzed using chi-square and logistic regression.Result: 153 respondents (81%) with low use of posyandu (0 - 7 times). Statistical tests showed that the age variable <30 years (p = 001. PR = 3,464), variable number of children under five (p = 0.041, PR = 3.509), under five age variables (p = 0.029, PR = 2.806), mother employment status variable ( p = 0.030, PR = 4.675), the mother's last education variable (p = 0.033, PR = 2,421), the mother's knowledge level variable (p = 0,000, PR = 9,100), and the mother's attitude variable (p = 0.005, PR = 3,077) . The knowledge level variable is the most dominant variable influencing the use of posyandu by toddlers aged 12-59 months. The researcher suggests that increasing the participation of all sectors in optimizing the implementation of posyandu.Conclusion : There is a relationship between maternal age, number of toddlers, toddler age, maternal employment status, last education, mother's level of knowledge and mother's attitude towards the use of posyandu